The 501Y.V2 SARS-CoV-2 variant has an intermediate viral load between the 501Y.V1 and the historical variants in nasopharyngeal samples from newly diagnosed COVID-19 patients. Issue 1 (July 2021) - Teyssou, Elisa; Soulie, Cathia; Visseaux, Benoit; Lambert-Niclot, Sidonie; Ferre, Valentine; Marot, Stéphane; Jary, Aude; Sayon, Sophie; Zafilaza, Karen; Leducq, Valentin; Schnuriger, Aurélie; Abdi, Basma; et al.
Highlights: Viral load in COVID-19 patient nasopharyngeal samples was different between variants. The 501Y.V2 variant had a viral load 2 times higher than the historical variants The 501Y.V2 variant had a viral load slightly lower than the 501Y.V1 The 501Y.V1 variant had a viral load 3-10 times higher than the historical variants A spread of the 501Y.V2 (lineage B1.351) into the world and specially in the United Kingdom (UK) has been reported by Tang et al. 1 . As the 501Y.V1 (lineage B1.1.7), which emerged in the UK 2, this variant notably present specific genetic patterns in the gene encoding the Spike protein (S). It was estimated that the 501Y.V1 presented a greater infectivity (up to 70%) and recent studies suggested a higher viral load (VL) for the 501Y.V1 as compared to the historical SARS-CoV-2 3, 4 . Currently, few data are available on the VL of the 501Y.V2. In France, these two variants are actively spreading into the population since late January and currently representing up to 70% of the new positive cases for the 501Y.V1 and 6% for the 501Y.V2 in Paris area.